Panazz Wins Third Crown - Davis, Rey (Trinidad Guardian)
Panazz Players beat off nine other steel band ensembles, to win the Pan Ramajay finals for the third time in a row.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago